The Role of E-Service Quality, Brand Awareness, and Customer value in Influencing Bukalapak Customer Satisfaction - Mamdukhah, Ghina; Nuvriasari, Audita (Journal of Humanities Education Management Accounting and Transportation, 2025)
This study aims to analyze the effect of e-service quality, brand awareness, and customer value on Bukalapak customer satisfaction. The sample in this study was 100 respondents who were determined by purposive sampling technique. The data collection method uses a questionnaire distributed online. The analytical tool used in hypothesis testing is multiple linear regression and hypothesis testing with the t test. The results of this study prove that: (1) E-Service Quality has no significant effect on Bukalapak Customer Satisfaction. (2) Brand Awareness has a positive and significant effect on Bukalapak Customer Satisfaction. (3) Customer Value has a positive and significant effect on Bukalapak Customer Satisfaction. These results have implications for the Bukalapak marketplace, especially in evaluating the level of customer satisfaction and designing marketing strategies to increase customer satisfaction.